A highly efficient chemical approach to producing green phosphorylated cellulosic macromolecules. Issue 39 (9th July 2021) - Ablouh, El-Houssaine; Brouillette, François; Taourirte, Moha; Sehaqui, Houssine; El Achaby, Mounir; Belfkira, Ahmed
Abstract : The introduction of phosphate groups into cellulosic fibers allows for the tuning of their fire resistance, chelating and metal-adhesion properties, enabling the development of flame-retardant adhesive and adsorbent materials. Abstract : The introduction of phosphate groups into cellulosic fibers allows for the tuning of their fire resistance, chelating and metal-adhesion properties, enabling the development of flame-retardant adhesive and adsorbent materials. Toward that end, the major challenge is developing a novel efficient and environmentally friendly phosphorylation route that offers an alternative to existing methods, which can achieve the targeted properties. For this purpose, cellulosic fibers were chemically modified herein using solid-state phosphorylation with phosphoric acid and urea without causing substantial damage to the fibers. The morphological, physicochemical, structural and thermal characterisations were examined using FQA, SEM, EDX, FTIR, 13 C/ 31 P NMR, conductometric titration, zeta potential measurement and thermogravimetric analysis. All the characterisations converge towards a crosslinked polyanion structure, with about 20 wt% grafted phosphates, a nitrogen content of about 5 wt% and a very high charge density of 6608 mmol kg −1 . Phosphate groups are linked to cellulose through a P–O–C bond in the form of orthophosphate and pyrophosphates. Furthermore, thermal properties of the phosphorylated cellulosic fibers were investigated and a new degradation mechanism was proposed.